2016
DOI: 10.14710/jksa.19.2.63-67
|View full text |Cite
|
Sign up to set email alerts
|

Sintesis dan Karakterisasi TiO2 Terdoping Nitrogen (N-Doped TiO2) dengan Metode Sol–Gel

Abstract: The wide bandgap energy of a TiO2 semiconductor equivalent to ultraviolet light (λ <380 nm) limits photocatalytic applications to confined to the ultraviolet region and not to the visible light region (λ = 400 nm-700 nm). In this research, the nitrogen oxide TiO2 synthesis was prepared by sol-gel method. The TiCl4 precursor was used as a source of titanium dioxide and CO(NH2)2 as a nitrogen source and is varied on the amount of N concentration with variations of 20 g, 30 g, 40 g and 50 g. The reflux was carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 7 publications
1
6
0
3
Order By: Relevance
“…At a certain point in the linear line that has been drawn there is an intersection point. This intersection point is called α. Α values are obtained using the Kubelka-Munk equation (Karim et al, 2016). The value of the ordinate point α from sample 1 to sample 5 can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…At a certain point in the linear line that has been drawn there is an intersection point. This intersection point is called α. Α values are obtained using the Kubelka-Munk equation (Karim et al, 2016). The value of the ordinate point α from sample 1 to sample 5 can be seen in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The PL emission analysis on the three SCDs/TiO2 samples showed that the composite with a CDs ratio of 0.5% has photocatalytic activity under light illumination with the highest efficiency, which corresponds to the Eg value. 5 1,53x10 7 2,6x10 11 1,92x10 7 Anthoni B. Aritonang *) , Ajuk Sapar, Heni Puspita Sari, Puji Ardiningsih, Adhitiyawarman Synthesis and Characterization of SCDs/TiO2 Composite CHEESA, 5(2), pp 92-100, 2022 | 97…”
Section: Photoluminescence (Pl)mentioning
confidence: 99%
“…A previous study reported that only 5% of UV light produced by the sun reaches the earth, while 45% is visible light [5]. This indicates that modifications are needed, such as the use of the photocatalytic activity of TiO2 in the visible light absorption region.…”
Section: Introductionmentioning
confidence: 99%
“…Where, F(R) is the Kubelka-Munk factor, S is the scattering coefficient, R is the measured reflectance value, A is the proportional constant, and Eg is the band gap [21]. For the measurement of current and voltage on the DSSC measured by a light source carried out in sunny conditions.…”
Section: Fig 3 Flowchart Of Sample Making and Characterizationmentioning
confidence: 99%